2016
DOI: 10.1007/s10578-016-0679-7
|View full text |Cite
|
Sign up to set email alerts
|

Parental Depression and Associations with Parenting and Children’s Physical and Mental Health in a Sub-Saharan African Setting

Abstract: Depression is one of the most prevalent mental health challenges in low- and middle-income countries. However, the mechanisms of parental depression on children’s development are understudied in these countries. This study examined the prevalence of parental depression, contextual predictors of parental depression, and the associations between parental depression, parenting and children’s development in one of the Sub-Saharan African countries-Uganda. Three hundred and three Ugandan parents of young children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…This suggests that food insecurity is not influencing children’s externalizing behavior problems via undernutrition, but possibly through increased psychological stress in the household. There is a larger evidence base supporting the negative effects of maternal depressive symptoms on children’s social-emotional development in LMIC [ 28 , 30 , 31 ]. A recent study in Pakistan, found that maternal depression during the prenatal period and when the child was seven years, were each linked to increased total behavioral difficulties on the SDQ [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that food insecurity is not influencing children’s externalizing behavior problems via undernutrition, but possibly through increased psychological stress in the household. There is a larger evidence base supporting the negative effects of maternal depressive symptoms on children’s social-emotional development in LMIC [ 28 , 30 , 31 ]. A recent study in Pakistan, found that maternal depression during the prenatal period and when the child was seven years, were each linked to increased total behavioral difficulties on the SDQ [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, food insecurity is a risk factor for maternal depression in LMICs (Wachs, ). After controlling for socio‐economic status, food insecurity was associated with caregiver psychosocial stress in Ethiopia (Hadley, Tessema, & Muluneh, ), parental depression in Uganda (Huang et al, ), and adverse child mental health in a review of LMICs (Herba, Glover, Ramchandani, & Rondon, ). Poor maternal mental health, in turn, has been associated with reduced child stimulation in Jamaica (Baker‐Henningham, Powell, Walker, & Grantham‐McGregor, ), infants' impaired motor development in Bangladesh (Nasreen, Kabir, Forsell, & Edhborg, ), and negative impacts on child growth in LMICs (Hurley, Surkan, & Black, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, household food security was associated with better language comprehension and expression after controlling for socioeconomic status (Saha et al, 2010). Food insecurity has also been linked to behaviours and conditions that can affect children's development, including maternal-infant interactions in Bangladesh (Frith, Naved, Persson, Rasmussen, & Frongillo, 2012) and parental depression, poor school functioning, and negative behavioural outcomes in Uganda (Huang, Abura, Theise, & Nakigudde, 2016).…”
mentioning
confidence: 99%
“…For example, the vast majority of teachers were motivated to learn about and implement the EBI and most schools and teachers have experience in child health promotion activities (Huang et al, 2014). In addition, among Ugandan families, positive parenting practices were related to fewer child behavior problems and better school outcomes (Huang, Abura, Theise, & Nakigudde, 2016). …”
Section: Introductionmentioning
confidence: 99%